Enriching the Conversation: Audience Perspectives on the Deliberative Nature and Potential of User Comments for News Media. Issue 4 (20th April 2020) - Engelke, Katherine M.
Abstract: While deliberation is regarded as crucial for democracies, research on the deliberative nature of user comments in journalism has so far been inconclusive and somewhat neglected to assess audience views qualitatively. Based on 26 in-depth interviews with German media users, this study therefore explores audience views on the deliberative nature and potential of user comments by examining their reasons for active and passive (non-)use, evaluations of comments and perceived personal and societal importance of comments. While users criticize a lack of deliberative or even non-deliberative elements and this drives them to not participate, to evaluate comments negatively and to not attribute personal value to comments, the findings also show that users recognize deliberative elements and that—when present—this deliberative nature is a reason for participation and positive evaluations. Users especially value the often unfulfilled or impeded deliberative potential of comments for society. Strategies to strengthen deliberation and future avenues of research are discussed.